2016
DOI: 10.1039/c5md00515a
|View full text |Cite
|
Sign up to set email alerts
|

Squaramides with cytotoxic activity against human gastric carcinoma cells HGC-27: synthesis and mechanism of action

Abstract: A series of squaramates and squaramides have been synthesized and their cytotoxic activity has been investigated in different cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…The cells in early apoptosis bind only to Annexin V, whereas dead and late stage apoptotic cells bind to both Annexin V-FITC and propidium iodide. 41 In this study, HeLa cells were treated with the compound 6d for 48 h at IC 50 concentrations to examine the apoptotic effect. It was observed that the compound 6d showed significant apoptosis against HeLa cells.…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 99%
“…The cells in early apoptosis bind only to Annexin V, whereas dead and late stage apoptotic cells bind to both Annexin V-FITC and propidium iodide. 41 In this study, HeLa cells were treated with the compound 6d for 48 h at IC 50 concentrations to examine the apoptotic effect. It was observed that the compound 6d showed significant apoptosis against HeLa cells.…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 99%
“…In the biological realm, squaramides have been used for specific cell labeling, to prepare active bioconjugates, or to replace the phosphate- and amide-type groups in bioisosteric replacements . In medicinal chemistry, cell-penetrating squaramides are known to exhibit significant anticancer and antiparasitic activity …”
Section: Introductionmentioning
confidence: 99%
“…Therefore it suggests that squaramides may serve as a good starting point for identifying the molecules which can specifically target cancer cells. Quintana et al 68 studied a series of squaramides and squaramates for antitumor activity against different cancer cells that confirms the antitumor properties of this class of promising drug candidates. Two cancer cell lines were used -HeLa (cervical carcinoma) and HGC-27 (human gastric cell line).…”
Section: Application Of Squaric Acid and Its Derivatives In Medicinementioning
confidence: 80%